Task-space control of industrial robot - Ang, Gary Poh Loong (2009)
According to Oxford dictionary, “robot” means a machine resembling and acting like a person. With the advancement of technology and engineering, robots have began to evolve, and is starting to mimic the way how human behaves and reacts to task and situation. In this project, some control laws are being utilized to reproduce how a human would react to a situation when a human wants to pick up an object. A human would normally reach out for the object with just a general direction without using his/her eyes. When his/her hand is near the vicinity of the object, he/she will use his/her eyes to guide the hand to pin-point the exact location of the object. In order to simulate how a human would reacts when trying to pick up an object, a SCARA robot with encoders is used to imitate a human arm and a camera is used to reproduce the feedback of the human eyes. The robot will be control in task-space, where by the robot is controlled using a given task instead of manually manipulating its trajectory. Beside that, the controllers together with the hardware of this system are tested for their robustness and reliability. As the system operates using a closed loop control, the feedback from the camera is crucial for the trajectory movement of the robot to be working perfectly. Thus the camera and controllers are tested for their robustness against depth uncertainties. Since the SCARA robot is use to simulate a human arm, the robot will be working in a 2-link state, which represents the upper arm and the forearm. The SCARA robot is then tested for its consistency when doing a trajectory movement when using only 2-links.